Analisis Peran BMT Dalam Pemberdayaan UMKM Melalui Pembiayaan Murabahah (Studi Kasus BMT Al-Ishlah Mitra Sejahtera) - Jakaria, Dandy; Wartoyo, Wartoyo; Iqbal, Moh (Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to find out the role of BMT AIMS in empowering MSMEs through murabahah financing. The subjects of this research are BMT managers, BMT staff and murabahah financing members. This type of research is field research with a descriptive approach method. The data sources obtained came from primary data, namely managers, staff and MSME murabahah members and secondary data, namely financing data and supporting documents. The data collection methods used were observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Testing the validity of the data used is observation, increasing persistence and triangulation. The triangulation used is triangulation of sources and techniques. Based on data analysis, it shows that the Cirebon branch of BMT AIMS plays a role in increasing the empowerment of MSMEs, namely first, capital assistance in the form of financing. Apart from that, the Cirebon branch of BMT AIMS increases empowerment by providing a pick-up service by meeting directly to withdraw savings and financing. Funding for facilities becomes BMT to empower MSMEs through murabahah financing. With this empowerment, members experience an increase in their assets in the form of merchandise inventory and an increase in the number of fixed assets in the form of shophouses. On the member turnover side, there has been an increase, on the other hand, income has increased, while on the stability side, the business is running well, their obligations and responsibilities can be paid on time and the installments do not burden them.